Optimalisasi Pembelajaran Bahasa Inggris melalui Buku Cerita Bergambar dan Bersuara di SD Virgo Maria 2 Bawen - Kisnanto, Yustina; Pulasari, Ines Asri Dwi; Septiningrum, Cornelia Betty; Siswanto, Anna Kezia; Putri, Aulia Kumalasari (LPPM UMRI, 2025)
The use of audiovisual aids (AVA) in teaching English to young learners has been shown to improve students’ understanding and motivation. To realize this, SD Virgo Maria 2 Bawen collaborated with a team of PBI UKSW lecturer and students in the program “Utilizing Audiovisual Aids to Teach English to Young Learners.” This community service program aims to support the English learning at this school by developing an AVA in the form of an illustrated and voiced storybook. The stages of this program include preparation, classroom observation and teacher interview, media design and making, media delivery and teacher training, and evaluation. By this program, the PBI UKSW team created an illustrated and voiced storybook entitled “In the Zoo” by catering the English teaching and learning needs of the fifth grade students at SD Virgo Maria 2 Bawen. The evaluation results show that the teacher can use the media practically and easily, and this media can increase the students’ motivation to learn English. There was also feedback on the audio clarity and narration speed. Overall, this program has made a positive contribution to improving the English teaching and learning at the primary level, especially at SD Virgo Maria 2 Bawen.